A novel technique for the synthesis of Au3N and its characterization using X-ray diffraction and Raman scattering techniques - S. Giri; P. Mallick; B. Mallick (AIP Advances)
We report a novel technique for the synthesis of Au3N via a solid-state diffusion-reaction mechanism. X-ray diffraction indexing confirmed that the structure of Au3N is anti-ReO3 with a lattice constant aAuN̄ of 4.065 ± 0.004 Å. The low value of lattice constant as compared to that of pristine gold, aAū of 4.080 ± 0.004 Å, is because of the LN2 quenching-induced structural squeezing. The structural squeezing caused compressive strain, leading to a compressed and rigid structure of Au3N. This is also supported by the shifting of characteristics, where the Raman peak shifted to the higher frequency side with an increased value of the full width at half maxima. The Raman shift of Au3N was found to be 1127.5 ± 0.3 cm−1, which is in good agreement with the theoretically calculated value obtained using density-functional theory. The prospects and future directions for the development of this novel gold nitride material are discussed.